Analysis of the Development and Utilization of a Tracer Study Website for Alumni and Students of IKIP PGRI Bojonegoro - Cuhanazriansyah, Muhammad Rinov; Ilmi, Moch Bil Barokah; Afrinta, Anida Cahya; Putri, Lusi Rahma Amelia (Journal of Manufacturing and Enterprise Information System, 2025)
This research focused on the critical role of tracer study in improving the quality of education and curriculum relevance at IKIP PGRI Bojonegoro. The main problem identified was the inadequate participation of alumni in completing tracer study surveys, which hindered the collection of reliable data regarding graduates' career outcomes. To address this issue, the study proposed the development of a web-based tracer study information system designed to facilitate data collection and enhance user engagement. The research utilized the Research and Development (R&D) methodology, which involved needs assessment, system design, and evaluation. The findings revealed that the implemented system significantly improved data collection efficiency, with 95% of respondents reporting that the interface was user-friendly. This indicated that integrating modern technology into tracer studies could effectively streamline data gathering and provide valuable career insights for alumni. The primary conclusion drawn from this research was that a web-based tracer study system could serve as an effective solution to enhance educational quality and better align graduates with industry demands in the context of the Fourth Industrial Revolution.